2005
DOI: 10.1086/431347
|View full text |Cite
|
Sign up to set email alerts
|

TRIDENT: An Infrared Differential Imaging Camera Optimized for the Detection of Methanated Substellar Companions

Abstract: A near-infrared camera in use at the Canada-France-Hawaii Telescope (CFHT) and at the 1.6-m telescope of the Observatoire du Mont-Mégantic is described. The camera is based on a Hawaii-1 1024×1024 HgCdTe array detector. Its main feature is to acquire three simultaneous images at three wavelengths across the methane absorption bandhead at 1.6 µm, enabling, in theory, an accurate subtraction of the stellar point spread function (PSF) and the detection of faint close methanated companions. The instrument has no c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 33 publications
0
107
0
Order By: Relevance
“…To our knowledge, this is the first time that such behavior is clearly demonstrated for an acquisition and reduction technique designed for speckle attenuation. The wall raised by quasistatic speckles that prevents a gain with longer integration time for standard observing techniques (Marois et al 2003(Marois et al , 2005Masciadri et al 2005) can thus be removed by ADI. Comparison with a classical imaging technique shows that ADI achieves 30 times better speckle attenuation in 30 minutes integration time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, this is the first time that such behavior is clearly demonstrated for an acquisition and reduction technique designed for speckle attenuation. The wall raised by quasistatic speckles that prevents a gain with longer integration time for standard observing techniques (Marois et al 2003(Marois et al , 2005Masciadri et al 2005) can thus be removed by ADI. Comparison with a classical imaging technique shows that ADI achieves 30 times better speckle attenuation in 30 minutes integration time.…”
Section: Resultsmentioning
confidence: 99%
“…The use of a multiwavelength instrument (Marois et al 2000(Marois et al , 2005Lafrenière et al 2004;Biller et al 2004) or an Integral Field Unit (IFU; Sparks & Ford 2002) to acquire simultaneous images at multiple wavelengths across the methane absorption band head at 1.6 m through the simultaneous spectral differential imaging (SSDI) technique (Racine et al 1999;Marois et al 2000Marois et al , 2005Biller et al 2004) could provide good short-lived and common-path speckle attenuations and increase detection limits. It has been shown that SSDI instruments are ultimately limited by non-common-path aberrations, which are expected to be stable over long periods of time, as they come almost entirely from the instrument itself (Marois et al 2005). Hence, the ADI technique nicely complements SSDI since it can be used to subtract the residuals caused by the non-commonpath aberrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This survey comprises two observational programs, both carried at Gemini-South, in Chile. The first uses NICI [2], a high-contrast imager, and takes advantage of Angular Differential Imaging (ADI [3]) and Spectral Differential Imaging (SDI [4]) to detect companions down to 2 M J up between 15 and 300 AU around the stars. Second epochs are currently being taken for this program, which surveyed over 40 stars.…”
Section: Introductionmentioning
confidence: 99%